Comparison of modified lingual split technique and conventional buccal bone cutting technique for the surgical extraction of impacted mandibular third molar - Kanwar Inderjot Singh; Atul Sharma; Amit Bali; Aayush Malhotra; Dinesh Chand Patidar; Kavita Tanwar (Wolters Kluwer Medknow Publications, 2019)
Objectives: The main objective of the study is to compare the modified lingual split technique and conventional buccal bone cutting technique for the surgical extraction of impacted mandibular third molar. Materials and Methods: Ten patients with bilaterally impacted third molars were randomly selected for the study. Technique selection for side will be done by coin tossing method for randomization. One side of each patient will be operated by conventional buccal bone cutting technique and other side will be operated by modified lingual split technique by Davis modification. Washout period will be of 2 weeks between the two surgical extractions. Various parameters were recorded intraoperatively and postoperatively. Results: Conventional buccal bone cutting technique took more time than modified lingual split technique, whereas no significant difference was found between the two techniques on comparing postoperative parameters such as trismus, dry socket, inflammation, and nerve paresthesia. Clinically, pain felt and swelling observed were less in modified lingual split technique as compared to conventional buccal bone cutting technique. Conclusion: It is been conclude that modified lingual split technique was less time-consuming, less painful, and less swelling was observed in comparison with conventional buccal bone cutting technique.